Identifikasi Kerusakan dan Perbaikan Lampu Taman Tenaga Surya di Universitas Bangka Belitung - Ihza Mahendra, Afdhal; Budianto, Tri Hendrawan; Jumnahdi, Muhammad (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2022)
The use of electrical energy from solar panels is sometimes not monitored properly, especially the solar garden lights at the University of Bangka Belitung where the overall condition of the solar garden lights is damaged. . Therefore, this research was conducted in order to find out the damage that often occurs in garden lights and how to repair the garden lights so that they function normally again. From the damage to the garden lights, they were divided into 3 categories of damage, namely lightly damaged, moderately damaged, and heavily damaged. After knowing the 3 categories of damage, an overall cost budget was made for the total components of the damaged goods, after knowing the cost budget, proceed to measure the efficiency value on clean and dirty solar panels without using a solar charger controller and using a solar charger controller. The efficiency of clean solar panels without a solar charger controller is 5.4% and lux is 21%, gross is 4.5% and lux is 20%. The efficiency of clean solar panels using a solar charger controller is 4.4% and lux is 22%, gross is 3.8% and lux is 21% Keywords: Current, Humidity, Solar Panels, Solar Radiation, Temperature, Voltage, Website